Insights into fluid migration during the 2021 La Palma eruption using seismic noise interferometry - Carvalho, Joana; Silveira, Graça; Mendes, Virgílio B.; Schimmel, Martin; Antón, Resurrección (Frontiers in Earth Science, 2024)
Ambient noise correlation analyses are largely used to monitor temporal medium changes, generally associated with stress field variations and/or fluid movement. Here we analyze the 2021 eruption of La Palma, the most active island in the Canary archipelago, to study its effects on the structure in a posteruptive stage. So far, most of the studies, whether in volcanic environments or other geological systems, focus on determining seismic velocity changes that can be associated to precursory signals.In our study, we are interested in localizing medium changes that permit to constrain the depth of the most affected structure and in suggesting possible mechanisms capable of induce such alterations.The auto-and cross-correlations functions were computed using the phase cross-correlation strategy. The correlations were linearly stacked with a 3-day sliding window. The combination of these two approaches proven to render the best results.The analysis of three years of data resulted in the detection of occasional decorrelation before the eruption, followed by a well-defined decoherence period after the eruption. In addition, the relationship between the waveform correlation and lag-time, using autocorrelations from before and after the eruption, permits to identify phase-shifts and waveform distortion, which are sensitive to different parameters and thus have great importance to infer on the possible mechanism. Phase-shifts occur when there is only velocity change, without changing the structure, whereas the waveform distortion is caused by a structural (geological) change.We were also able to infer about the depths where the most significant medium alterations occur. We observed that the decorrelation occurs at lag-times corresponding to changes localized in depth. The surface structure appears to not have undergone significant medium changes for depths until about 8 km, either before or after the eruption.